SAFA initiates innate immunity against cytoplasmic RNA virus SFTSV infection - Bin-yan Liu (Public Library of Science (PLoS), 2021)
Nuclear scaffold attachment factor A (SAFA) is a novel RNA sensor involved in sensing viral RNA in the nucleus and mediating antiviral immunity. Severe fever with thrombocytopenia syndrome virus (SFTSV) is a bunyavirus that causes SFTS with a high fatality rate of up to 30%. It remains elusive whether and how cytoplasmic SFTSV can be sensed by the RNA sensor SAFA. Here, we demonstrated that SAFA was able to detect SFTSV infection and mediate antiviral interferon and inflammatory responses. Transcription and expression levels of SAFA were strikingly upregulated under SFTSV infection. SAFA was retained in the cytoplasm by interaction with SFTSV nucleocapsid protein (NP). Importantly, SFTSV genomic RNA was recognized by cytoplasmic SAFA, which recruited and promoted activation of the STING-TBK1 signaling axis against SFTSV infection. Of note, the nuclear localization signal (NLS) domain of SAFA was important for interaction with SFTSV NP and recognition of SFTSV RNA in the cytoplasm. In conclusion, our study reveals a novel antiviral mechanism in which SAFA functions as a novel cytoplasmic RNA sensor that directly recognizes RNA virus SFTSV and mediates an antiviral response. Author summary Severe fever with thrombocytopenia syndrome virus (SFTSV) is an RNA virus with a high fatality rate of up to 30%, which replicates exclusively in the cytoplasm. To date, many cytoplasmic RNA sensors were known to recognize SFTSV infection and trigger antiviral immune responses. Nuclear scaffold attachment factor A (SAFA) is a novel nuclear RNA sensor which can sense viral RNA in the nucleus and promote activation of antiviral immunity. However, there are no studies to investigate whether SAFA could detect cytoplasmic RNA virus infection. Here, we reported that SAFA was able to detect RNA virus SFTSV invasion. Under SFTSV infection, SAFA was retained in the cytoplasm and recognized SFTSV infection by interaction with SFTSV nucleocapsid protein (NP) and cytoplasmic SFTSV RNA directly. Importantly, SAFA recruited and promoted the activation of the STING-TBK1 signaling pathway-mediated antiviral immunity to suppress SFTSV infection. This study provides a further acquaintance in SAFA-mediated antiviral immune responses, illustrating the novel role of SAFA in sensing cytoplasmic SFTSV and mediates an antiviral response.